Engaging Summer School Programme’s Participants in Reflective Learning (Sains Humanika, 2017)
Experiencing studying in one’s home country might be different from experiencing it in a host country. Hence, to help Japanese students who participate in the two-week Universiti Teknologi Malaysia (UTM) ESL summer school programme achieve their goals to better communicate in English and to experience an academic life in UTM, many in-class and out-of-class activities and tasks were conducted and organized for them. One of the out-of-class task was the half-day classroom visit designed based on the foundation of reflective learning where the participants had to attend their UTM buddies classes. While in the classrooms, they were encouraged to participate in the class activities. They were also required to write their own reflections on the visit in their journals. Once the task was completed, they were required to share their experience in a group discussion activity. From the analysis of both their written and oral reflections, it was found that many of the participants claimed that there were differences between the Japanese and UTM classrooms with regard to the teaching methods and the UTM students’ classroom behaviour. These findings revealed that the specifically designed half-day classroom visit had stimulated the participants to recognize their personal values, to build their confidence and to maximize their learning experience. The aim of this paper is, therefore, to share the summer school participants’ reflections on their experiences undergoing the half-day classroom situation in UTM.
Keywords: Reflective learning; ESL; summer school; buddy system; classroom visit.